283 Does a Pen and Paper Assessment of Executive Skills Correlate with Functional Decline Identified Through Specialised Occupational Therapy Assessment?. (16th September 2019) - Tobin, Fiona; McGuinn, Caitriona; Pearson, Corinne; Dooky, Joshi; McHale, Cathy; Coughlan, Tara; O'Neill, Desmond; Ryan, Daniel; Collins, Ronan; Kennelly, Sean
Abstract: Background: Executive skills refer to a set of cognitive skills that allow individuals to engage in goal directed behavior. They encompass planning, initiation, inhibition, monitoring and flexibility in approach to tasks, and are necessary for functional competence. Executive skills are vulnerable to disruption with damage to the brain, as occurs with dementia. Methods: Participants were recruited from a tertiary memory assessment and support Service. The Assessment of Motor & Process Skills (AMPS), a standardised observational assessment of occupational performance ( 1 Fischer, 2003) was administered by trained Occupational Therapists. In addition, the EXIT-25, a pen & paper based assessment of executive skills ( 2 Royall et al, 1992) was administered. Process scores from the AMPS, and overall score from the EXIT 25 were utilised for correlation analysis. Results: 22 participants, 12 male and 10 females, age range 60-91 (mean 75.5 years), was analysed using Spearman's Rho correlation (-.2). Results did not identify a strong correlation Conclusion: Dementia is commonly regarded as a disorder of memory. However, diagnosis is dependent on functional decline related to cognitive decline. The AMPS provides a formal assessment of functional skills, in terms of motor & process skills with cut off scores regarding safe independent living. The results of this study indicate that the AMPS is not associated with executive scores on formal cognitive assessments, highlighting the value of an extensive multi-component MDT approach (also incorporating history taking, imaging, bio marker testing etc.) in assessing and diagnosing a dementia.